Early and unexpectedly severe start of influenza epidemic in the Czech Republic during influenza season 2012-13 - Kyncl, J; Havlickova, M; Nagy, A; Jirincova, H; Piskova, I (Euro surveillance, 2013)
A sudden increase in severe influenza has been registered in the Czech Republic since the end of 2012, with 264 cases requiring intensive care, including 51 deaths. Most patients had at least one risk factor. Severe influenza in patients with obesity, smoking and/or haematological disorders including haematological cancers was more frequent than in the pre-pandemic period. The seasonal influenza vaccination status of the cases indicates indirect efficiency of the current vaccine in preventing severe influenza.
Keywords: novorozenec; Infant, Newborn; RNA virová; surveillance populace; Infant; Humans; kojenec; lidé středního věku; dítě; Sequence Analysis, DNA; Influenza A virus; Influenza, Human; Child; Epidemics; Female; rizikové faktory; mladý dospělý; dospělí; Aged; Hemagglutination Inhibition Tests; virus chřipky A; Influenza Vaccines; senioři; lidé; časové faktory; vakcíny proti chřipce; předškolní dítě; sekvenční analýza DNA; Adult; chřipka lidská; roční období; ženské pohlaví; stupeň závažnosti nemoci; jednotky intenzivní péče; Male; Middle Aged; Adolescent; Seasons; polymerázová řetězová reakce; Czech Republic; Polymerase Chain Reaction; testy inhibice hemaglutinace; Severity of Illness Index; epidemie; RNA, Viral; Young Adult; Population Surveillance; Intensive Care Units; Česká republika; mužské pohlaví; Child, Preschool; Time Factors; mladiství; Risk Factors